2022
DOI: 10.1007/s12672-022-00506-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a breast cancer prognosis model based on alternative splicing and immune infiltration

Abstract: Background Breast cancer (BC) is the most common malignancy among women in the world. Alternative splicing (AS) is an important mechanism for regulating gene expression and producing proteome diversity, which is closely related to tumorigenesis. Understanding the role of AS in BC may be helpful to reveal new therapeutic targets for clinical interventions. Methods RNA-seq, clinical and AS data of TCGA-BRCA were downloaded from TCGA and TCGA SpliceSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…26 However, previous studies mainly focused on constructing prognostic models using single oxidative stress or immune features, which often suffer from limitations in robustness and generalizability. [27][28][29][30] In order to address these limitations, our study takes a comprehensive approach by incorporating both immune-related and oxidative stress-related lncRNAs. By encompassing multiscale clinical features, we aim to improve the accuracy and robustness of prognostic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, previous studies mainly focused on constructing prognostic models using single oxidative stress or immune features, which often suffer from limitations in robustness and generalizability. [27][28][29][30] In order to address these limitations, our study takes a comprehensive approach by incorporating both immune-related and oxidative stress-related lncRNAs. By encompassing multiscale clinical features, we aim to improve the accuracy and robustness of prognostic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that SH2B3 contributes to glioblastoma progression by transducing IL-6/gp130/STAT3 signaling ( Cai et al, 2021 ). TTC39C has been screened as an alternative splicing-related mRNA that is implicated in tumor microenvironment and immune infiltration of BRCA mutation patients ( Zhang et al, 2022a ). LncRNA SNHG8 promotes breast cancer progression and sponged miR-634, leading to the upregulation of ZBTB20 ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent year, algorithms have been developed to predict tumor purity using gene expression data based on the TCGA database. For example, (36,37), breast cancer (38,39), colorectal cancer (40)(41)(42) and hepatocellular carcinoma (43), which demonstrated that such big-data-based algorithms are effective, although its utility on immune and/or stromal scores in glioblastoma multiforme (GBM) has not been explored in detail.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%